Base‐Controlled Selectivity in the Synthesis of Linear and Angular Fused Quinazolinones by a Palladium‐Catalyzed Carbonylation/Nucleophilic Aromatic Substitution Sequence1. (30th May 2014) - Chen, Jianbin; Natte, Kishore; Spannenberg, Anke; Neumann, Helfried; Langer, Peter; Beller, Matthias; Wu, Xiao‐Feng
Abstract A new approach for the facile synthesis of fused quinazolinone scaffolds through a palladium‐catalyzed carbonylative coupling followed by an intramolecular nucleophilic aromatic substitution is described. The base serves as the key modulator: Whereas DBU gives rise to the linear isomers, Et3N promotes the preferential formation of angular products. Interestingly, a light‐induced 4+4 reaction of the product was also observed.